Tangible Prayer in Early Judaism and Early Christianity - Moses, Robert E. (2015)
Both the Jewish and Christian faiths view prayer as dialogue with the God of Israel. Prayer assumes that God is near to those in need and is attentive to the cries of the saints. Those who pray to God can hope and believe that God will hear or acknowledge their prayers. Yet there exists a tradition in both early Judaism and early Christianity, especially in apocalyptic thought but not exclusive to it, that views prayers as something tangible and, therefore, requiring an intermediary to transport and present before God. This notion of prayer complicates the assumption that God hears all prayers, for according to this tradition the angel bearing the prayers of the saints and/or God's response to the prayers may face obstacles while transporting the prayers to God or God's response to humans.
Keywords: Prayer; Angels; Apocalyptic; Intermediaries; Sacrifice; Temple